(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This study examined the writing skill of the students at the undergraduate level, with a special focus on the use of prepositions of place, time and direction in English. The subjects of the study comprised of 100 randomly selected undergraduate students of English literature from two Arts and Science colleges located in Coimbatore city. The data elicitation instrument was a guided cloze test in which the subjects were asked to fill the gaps using appropriate prepositions of place, time and direction. To analyze the collected data, socio-linguistic and descriptive methods were used. The results indicated that the students found more difficulties in the use of prepositions of place and direction than the prepositions of time because of their mother tongue interference. The findings imply that teachers should pay more attention while teaching the prepositions of place, time and direction and provide sufficient explanations about them to the students in the classroom.